Diagnosa Penyakit Bells Palsy Menerapkan Metode Tsukamoto - Cyntia Lasmi Andesti; Weri Sirait (Journal of Science and Technology, 2022)
Bell’s Palsy is paralysis of the facial muscles that causes one side of the face which causes one side of the face to sag. In Indonesia, there are many cases of bell's palsy but it is definitely difficult to determine. In this case, there was a case of bell's palsy in Indonesia of 19.55%, from all the most frequent cases of neuropathy that were found in the age of 20-50 years, and the incidence increased with increasing age after 60 years. About 60-85% of sufferers can recover completely within 3 weeks and only 15% require 3 months. But there are 30% of those who have a lifetime disability due to the patient not getting better for 4 months. Therefore an expert system was designed to diagnose bells palsy. The method used in the expert system is the Tsukamoto Method. The Tsukamoto method is a development of the Mamdani and Sugeno methods which use control and are also used by humans instead of machines. Fuzzy Tsukamoto is one method that is very flexible and has a tolerance for existing data. This expert system can provide solutions and ways to prevent bell's palsy with the diagnosis process carried out efficiently and save time in helping the general public in the prevention that occurs. This web-based expert system application was built with the PHP programming language and MySQL data storage